Legal Guidance on When Schools Can Remove Students for Exhibiting Dangerous Behaviors Through Injunctive Relief. (April 2018) - Counts, Jennifer; Katsiyannis, Antonis; Beard, Jenna
Violence in schools remains a complex and challenging issue. In this article, we examine schools' responsibilities in placement and the provision of services for students who have chronically exhibited dangerous behaviors. Multiple court cases have provided schools guidance in evaluating when student removal through injunctive relief for dangerous behavior is warranted. A four-point criterion for informing removal decisions is discussed along with some practical implications for administrators.